K-theoretic wall-crossing formulas and multiple basic hypergeometric series - Ohkawa, R.; Shiraishi, J. (Journal of algebra, 2025)
We study K-theoretic integrals over framed quiver moduli via wall-crossing phenomena. We study the chainsaw quiver varieties, and consider generating functions defined by two types of K-theoretic classes. In particular, we focus on integrals over the handsaw quiver varieties of type A1, and get functional equations for each of them. We also give explicit formula for these partition functions. In particular, we obtain geometric interpretation of transformation formulas for multiple basic hypergeometric series including the Kajihara transformation formula, and the one studied by Langer-Schlosser-Warnaar and Hallnäs-Langman-Noumi-Rosengren.